Al-Dalālāt al-Kināʾiyyah fī al-Qurʾān al-Karīm wa Tawẓīfuhā fī Tadrīs al-Lughah al-ʿArabīyah (Dirāsah Uslūbīyah wa-Tadāwulīyah) - Saepurrohman, Aep; M Yunus, Badruzzaman; Syafei, Isop (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2026)
The Qur'an exhibits a distinctive linguistic style characterized by various rhetorical techniques, including kināyah (euphemism), used to convey divine messages with subtlety and refinement. This study explores the use of kināyah in the Qur'an from both stylistic and pragmatic perspectives and examines its implementation in Arabic language teaching. The research aims to provide an overview of kināyah in the Qur'an, identify its linguistic features through stylistic and pragmatic analysis, and highlight its pedagogical relevance. Theoretically, kināyah is seen as an elegant form of expression that stylistically involves word choice and placement, while pragmatically relating to communicative function, implicature, and speech acts. Using a qualitative approach and descriptive methods, the study employs content and discourse analysis. Key findings include: (a) the Qur'an presents kināyah across various themes—such as morality, psychological traits, and eschatology; (b) stylistically, it reveals semantic deviation and rhetorical strength; (c) pragmatically, it reflects implicit meanings and performative force; and (d) the study of kināyah offers valuable insights for enhancing Arabic language instruction.